Focal Pulsed Field Ablation for Pulmonary Vein Isolation and Linear Atrial Lesions: A Preclinical Assessment of Safety and Durability - Koruth, Jacob S; Kuroki, Kenji; Kawamura, Iwanari; Stoffregen, William C; Dukkipati, Srinivas R; Neuzil, Petr; Reddy, Vivek Y (Circulation. Arrhythmia and electrophysiology, 2020)
BACKGROUND: A novel ablation and mapping system can toggle between delivering biphasic pulsed field (PF) and radiofrequency energy from a 9-mm lattice-tip catheter. We assessed the preclinical feasibility and safety of (1) focal PF-based thoracic vein isolation and linear ablation, (2) combined PF and radiofrequency focal ablation, and (3) PF delivered directly atop the esophagus. METHODS: Two cohorts of 6 swine were treated with pulsed fields at low dose (PFLD) and high dose (PFHD) and followed for 4 and 2 weeks, respectively, to isolate 25 thoracic veins and create 5 right atrial (PFLD), 6 mitral (PFHD), and 6 roof lines (radiofrequency+PFHD). Baseline and follow-up voltage mapping, venous potentials, ostial diameters, and phrenic nerve viability were assessed. PFHD and radiofrequency lesions were delivered in 4 and 1 swine from the inferior vena cava onto a forcefully deviated esophagus. All tissues were submitted for histopathology. RESULTS: Hundred percent of thoracic veins (25 of 25) were successfully isolated with 12.4±3.6 applications/vein with mean PF times of <90 seconds/vein. Durable isolation improved from 61.5% PFLD to 100% with PFHD (P=0.04), and all linear lesions were successfully completed without incurring venous stenoses or phrenic injury. PFHD sections had higher transmurality rates than PFLD (98.3% versus 88.1%; P=0.03) despite greater mean thickness (2.5 versus 1.3 mm; P<0.001). PF lesions demonstrated homogenous fibrosis without epicardial fat, nerve, or vessel involvement. In comparison, radiofrequency+PFHD sections revealed similar transmurality but expectedly more necrosis, inflammation, and epicardial fat, nerve, and vessel involvement. Significant ablation-related esophageal necrosis, inflammation, and fibrosis were seen in all radiofrequency sections, as compared with no PF sections. CONCLUSIONS: The lattice-tip catheter can deliver focal PF to durably isolate veins and create linear lesions with excellent transmurality and without complications. The PF lesions did not damage the phrenic nerve, vessels, and the esophagus.
Keywords: Models, Animal; Sus scrofa; Postoperative Complications; vena cava, superior; atrial fibrillation; Heart Rate; catheter ablation; Therapeutic Irrigation; srdeční frekvence; pooperační komplikace; Catheter Ablation; srdeční síně; Pulmonary Veins; Animals; akční potenciály; Action Potentials; Cardiac Catheters; ženské pohlaví; pulmonary veins; zvířata; léčebná irigace; modely u zvířat; Electrophysiologic Techniques, Cardiac; venae pulmonales; elektrofyziologické techniky kardiologické; katetrizační ablace; Female; catheters; studie proveditelnosti; srdeční katétry; Heart Atria; Feasibility Studies